Rat liver mitochondrial dysfunction by addition of copper(II) or iron(III) ions - Saporito Magriñá, Christian Martín (2017)
Increased copper (Cu) and iron (Fe) levels in liver and brain are associated to oxidative stress and damage with increased phospholipid oxidation process. The aim of this work was to assess the toxic effects of Cu2 + and Fe3 + addition to rat liver mitochondria by determining mitochondrial respiration in states 3 (active respiration) and 4 (resting respiration), and phospholipid peroxidation. Both, Cu2 + and Fe3 + produced decreases in O2 consumption in a concentration-dependent manner in active state 3: both ions by 42% with malate-glutamate as complex I substrate (concentration for half maximal response (C50) 60 μM Cu2 + and 1.25 mM Fe3 +), and with succinate as complex II substrate: 64?69% with C50 of 50 μM Cu2 + and with C50 of 1.25 mM of Fe3 +. Respiratory control decreased with Cu2 + (C50 50 μM) and Fe3 + (C50 1.25-1-75 mM) with both substrates. Cu2 + produced a 2-fold increase and Fe3 + a 5-fold increase of thiobarbituric acid-reactive substances (TBARS) content from 25 μM Cu2 + (C50 40 μM) and from 100 μM Fe3 + (C50 1.75 mM). Supplementations with Cu2 + and Fe3 + ions induce mitochondrial dysfunction with phospholipid peroxidation in rat liver mitochondria. Although is proved that a Fenton/Haber Weiss mechanism of oxidative damage occurs in metal-ion induced mitochondrial toxicity, slightly different responses to the metal ions suggest some differences in the mechanism of intracellular toxicity. The decreased rates of mitochondrial respiration and the alteration of mitochondrial function by phospholipid and protein oxidations lead to mitochondrial dysfunction, cellular dyshomeostasis and cell death.